Development of STEM-based worksheets to improve critical thinking on matter topic - Edi Siswanto; Ashar Hasairin; Sumarno Sumarno (Inovasi Kurikulum, 2025)
This study aims to develop a STEM-based Student Worksheet (LKPD) for Science and Social Studies (IPAS) subject in the fourth grade of elementary school, focusing on the topic of various forms of matter and their changes. The research employed a Research and Development (R&D) method using the ADDIE model, which includes analysis, design, development, implementation, and evaluation phases. Expert validations were conducted by content, media, and language specialists to assess the quality of material, visual design, and linguistic accuracy. All validation results were categorized as highly valid. Practicality testing was conducted through teacher and student responses as well as small and large group trials, which showed the LKPD to be highly practical in the learning process. Effectiveness was confirmed through increased learning outcomes in the experimental group compared to the control group, supported by independent t-tests and N-Gain analysis. The findings indicate that the STEM-based LKPD enhances students' critical thinking skills. The developed product also aligns with constructivist, behaviorist, and cognitive learning theories. The results confirm that the STEM-based LKPD meets the criteria of validity, practicality, and effectiveness, making it suitable for implementation in IPAS learning at the elementary level.   Abstrak Keterampilan berpikir kritis peserta didik sekolah dasar masih tergolong rendah, terutama saat mempelajari materi perubahan wujud benda. Kondisi ini menuntut ketersediaan perangkat pembelajaran yang dirancang secara kontekstual, sistematis, dan terintegrasi. Tujuan dari penelitian ini adalah mengembangkan Lembar Kerja Peserta Didik (LKPD) berbasis pendekatan STEM untuk meningkatkan kemampuan berpikir kritis pada mata pelajaran IPAS kelas IV sekolah dasar. Proses pengembangan mengikuti model ADDIE yang mencakup tahap analisis, desain, pengembangan, implementasi, dan evaluasi. Penilaian dilakukan melalui validasi oleh para ahli, angket kepraktisan dari guru dan peserta didik, serta pengukuran efektivitas menggunakan soal pretes dan postes. Hasil validasi menunjukkan bahwa LKPD yang dikembangkan sangat layak digunakan berdasarkan aspek isi, kebahasaan, dan desain tampilan. Respon guru dan peserta didik menunjukkan bahwa LKPD tersebut mudah digunakan dan menarik secara visual maupun fungsional. Evaluasi efektivitas menunjukkan peningkatan keterampilan berpikir kritis peserta didik secara signifikan setelah penggunaan LKPD berbasis STEM dalam proses pembelajaran. Hasil ini menunjukkan bahwa LKPD yang dikembangkan tidak hanya valid dan praktis, tetapi juga memberikan dampak positif terhadap pencapaian hasil belajar peserta didik. Penelitian ini merekomendasikan penggunaan LKPD berbasis STEM sebagai media pembelajaran yang mendorong keterampilan berpikir kritis sejak jenjang pendidikan dasar. Kata Kunci: berpikir kritis; IPAS; LKPD; STEM